Synthesis of porous Pd nanoparticles by therapeutic chaga extract for highly efficient tri-modal cancer treatment. Issue 42 (18th October 2018) - Gil, Yeong-Gyu; Kang, Seounghun; Chae, Ari; Kim, Young-Kwan; Min, Dal-Hee; Jang, Hongje
Abstract : Porous palladium nanoparticles were designed and synthesized to maximize the pharmacological activity of the chaga mushroom ( Inonotus obliquus ) extract, which has anticancer and antibacterial activities. Abstract : Porous palladium nanoparticles were designed and synthesized to maximize the pharmacological activity of the chaga mushroom ( Inonotus obliquus ) extract, which has anticancer and antibacterial activities. In the present study, we synthesized anisotropic porous Pd nanostructures with ultraviolet-visible-near infrared whole wavelength region absorption using chaga extract concentration-dependent reductant-mediated synthesis. The porous Pd nanoparticles exhibited a surface chaga extract-derived anticancer effect, controlled delivery of doxorubicin through electrostatic interaction, and a photothermal conversion effect under 808 nm laser irradiation. The combined application of the three cancer treatment approaches clearly demonstrated the feasibility of synergistic tri-modal therapy. The present platform using Pd, which is a key constituent element of nanocatalysts but is not commonly used in biological applications, suggests numerous applications utilizing Pd nanostructures, as well as the potential development of new cancer therapies.